The relationship between functional living status and perceived social support in patients with cancer - Seda Karaman; Elanur Yılmaz-Karabulutlu (Nursing Practice Today, 2016)
Background & Aim: Cancer is a significant and global health problem that negatively affects the functional status. The aim of this study was to investigate the relationship between perceived social support, functional status and demographic characteristics in cancer patients.